2021
DOI: 10.1155/2021/2675786
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Application of Interactive English‐Teaching Mode under Complex Data Analysis

Abstract: This research takes vocabulary learning in college English courses as an entry point and investigates the interrelationship between college students and electronic media, the presentation of interactive English-teaching content in college English, and the effect of different English-teaching modes on the effect of vocabulary learning through empirical methods in the form of network multimedia. This study provides ideas for an in-depth understanding of the incongruities that exist between interactive English te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…This is following the previous research done which found that integrating technology and reinforcing ICT in language classes had a significant impact on learning enhancement (Asad et al. , 2021; Xu and Tsai, 2021; Fu, 2013). In the Internet era, students have more access to extensive, genuine, rich and lively resources (Wang and Liu, 2015; Wang et al.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This is following the previous research done which found that integrating technology and reinforcing ICT in language classes had a significant impact on learning enhancement (Asad et al. , 2021; Xu and Tsai, 2021; Fu, 2013). In the Internet era, students have more access to extensive, genuine, rich and lively resources (Wang and Liu, 2015; Wang et al.…”
Section: Discussionsupporting
confidence: 84%
“…The global education system reinforced the use of ICT in language classes, therefore; many teachers and educators have integrated technology, including the World Wide Web (WWW), into their teaching (Asad et al. , 2021; Xu and Tsai, 2021; Fu, 2013). However, there has been a lack of studies conducted to provide educators with a tangible answer to the perfect way to integrate teaching/learning methods.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Network Foundation. In college English teaching, the weak English foundation of students has always been a difficult point of teaching and a major causal factor that hinders English teachers from improving the quality of teaching [9]. In the offline classroom, due to the limitation of teaching time and teachers' energy, only uniform teaching contents can be designed, and differentiated teaching methods are more difficult to implement in reality.…”
Section: Rational Design Of Teaching Contents Based On Mobilementioning
confidence: 99%
“…A lot of research has also been carried out on the research of English teaching methods [10]. Xu and Tsai [11] took the difficulties in college students English vocabulary learning as the research breakthrough point; they analyzed the relationship between college students and electronic media and the impact of interactive teaching mode on college students' vocabulary memory. At the same time, they studied the theory of multimedia-based interactive English teaching mode and intervention model for English learning adaptation.…”
Section: Introductionmentioning
confidence: 99%